تأثير الترسبات الجزيئية في كفاءة المبادلات الحرارية - حبيب ربيع (Latakia University Journal -Engineering Sciences Series, 2019)
The previous work proves that there is no reliable correlation to predict particulate fouling effect on heat exchangers performance. The main objective of this work is to develop a semi-empirical model for heat exchanger fouling.. The available experimental data are analyzed and then used to establish the proposed model. This model accounts for the effects of flow conditions on fouling. Resistance to predict the design, operation and performance parameters of plate type heat exchangers. It is found that the exchanger effectiveness decrease by 11% to 32.5% due to fouling of the present conditions. Also, the predicted pressure drop with fouling is higher than that of the clean fluids by 15% to 75% for the same conditions. Therefore, extra power and initial operating costs are needed. The present model can be used to document the design parameters of plate type, double pipe, and similar heat exchangers. تبين مما سبق أنه لا توجد علاقة عامة أو موثقة لدراسة تأثير الترسبات الجزئية في أداء المبادلات الحرارية. الهدف الرئيس من البحث الحالي هو تطوير نموذج شبه عملي لدراسة تأثير الترسيب في أداء المبادلات الحرارية والتنبؤ بزمن فترات التنظيف المتعاقبة. لقد تم تقييم نتائج الأبحاث التجريبية السابقة وتحليلها لاستنتاج النموذج المقترح مع الأخذ بعين الاعتبار تأثير ظروف الجريان مثل السرعة، التركيز، و التدفق الحراري في مقاومة الترسيب، معامل انتقال الحرارة الإجمالي، مساحة سطح التسخين، كفاءة المبادل و الفقد في الضغط، الخ. تم تطبيق النموذج الرياضي على مبادلات حرارية من النوع الصفائحي لدراسة عناصر التصميم والأداء ضمن مجال واسع لظروف التشغيل. أثبت البحث أن كفاءة المبادل الحراري تتناقص تقريبا بمقدار 11% إلي 32.5% في ظل ظروف التشغيل الحالية نتيجة هذه الترسبات, كما تم التنبؤ بقيمة الفقد في الضغط الناتج عن هذه الترسبات, والتي تزداد عن مثيلتها في الحالة النظيفة تقريبا بمقدار 15% إلي 75% في ظل ظروف التشغيل نفسها، من أجل ذلك يحتاج نظام الضخ إلي طاقة إضافية وبالتالي تكلفة تشغيل.